2020
DOI: 10.1051/0004-6361/202038337
|View full text |Cite
|
Sign up to set email alerts
|

The circumstellar environment of EX Lupi: SPHERE and SINFONI views

Abstract: Context. EX Lup is a well-studied T Tauri star that represents the prototype of young eruptive stars known as EXors. They are characterized by repetitive outbursts that are due to enhanced accretion from the circumstellar disk onto the star. In this paper, we analyze new adaptive optics imaging and spectroscopic observations to study EX Lup and its circumstellar environment in near-infrared in its quiescent phase. Aims. We aim to provide a comprehensive understanding of the circumstellar environment around EX … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…EXors also brighten by a few magnitudes, but unlike FUors, they remain in the high brightness stage for a few months to a few years. Observations of repetitive outbursts are almost the rule for the majority of EXors, e.g., EX Lup (Rigliaco et al 2020) and V1647 Ori (Ninan et al 2013). Another major difference between the two classifications is the rich emission line spectrum found in EXors (Herbig 2007;Aspin et al 2010;Kóspál et al 2011a;Audard et al 2014;Hodapp et al 2019Hodapp et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…EXors also brighten by a few magnitudes, but unlike FUors, they remain in the high brightness stage for a few months to a few years. Observations of repetitive outbursts are almost the rule for the majority of EXors, e.g., EX Lup (Rigliaco et al 2020) and V1647 Ori (Ninan et al 2013). Another major difference between the two classifications is the rich emission line spectrum found in EXors (Herbig 2007;Aspin et al 2010;Kóspál et al 2011a;Audard et al 2014;Hodapp et al 2019Hodapp et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…In this reduction of the NACO data, many of the nondetections are likely the result of small or faint disks, or the absence of polarised light. Notably, IM Lup, GQ Lup, and EX Lup do not show polarised light in the NACO data, despite their prominent detections with SPHERE/IRDIS (Avenhaus et al 2018;van Holstein et al 2021;Rigliaco et al 2020). The data of IM Lup and GQ Lup were not previously published, whereas Kóspál et al (2011)…”
Section: Identification Of Detectionsmentioning
confidence: 83%
“…The amplitude of 2019 brightening is higher than 4.8 mag, the largest burst in Gaia19fct, and is categorized as an outburst (ΔV = ∼ 2.5−6 mag; Fischer et al 2022). The high amplitude is similar to what is typical for FUors (Fischer et al 2022, and references therein), as well as the most powerful outbursts found in EXors (EX Lup, Ábrahám et al 2019;Rigliaco et al 2020;Gaia20eae, Cruz-Sáenz de Miera et al 2022a;Ghosh et al 2022). The peak brightness was reached in 2019 December within ∼70 days since the beginning of the outburst (2019 October), resulting in a steep rising rate of −0.072 mag day −1 .…”
Section: Light Curvementioning
confidence: 89%